Extracellular synthesis of silver nanoparticles using living peanut seedling - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Applied Nanoscience, 2014)
Synthesis of nanoparticles by environment friendly method is an important aspect of nanotechnology. In the present study, extracellular reduction of silver ions to silver nanoparticles was carried out using living peanut plant. The electron microscopic analysis shows that the formed nanoparticles were of different shapes and sizes. The formed nanoparticles were polydispersed. The shapes of the nanoparticles were spherical, square, triangle, hexagonal and rod. Most of the particles were spherical and 56 nm in size. EDS analysis confirmed the formed nanoparticles were of silver. The crystalline nature of nanoparticles was confirmed by diffraction. This method opens up an exciting possibility of plant-based synthesis of other inorganic nanomaterials. This study confirms the synthesis of extracellular silver nanoparticles by living plant.
Keywords: Nanoparticles; Shapes; Silver; synthesis; TEM

Living plant-mediated synthesis of different shaped gold nanoparticles - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Nanoscience and Nanotechnology Letters, 2014)
We demonstrate extracellular green synthesis of gold nanoparticles with different shapes and sizes by using live Prosopis juliflora L. seedling. The conversion of ionic to metallic gold nanoparticles by P. juliflora seedling was carried out in short period. The formed nanoparticles were characterized by UV, TEM, Diffraction and EDS. TEM shows well dispersed particles of different shapes and sizes. The percentage of different shapes of nanoparticles was calculated, most of the particles were spherical in shape (75%). The triangle nanoparticles were 10%, followed by squares (8%), hexagonal (5%) and rods (2%). The diffraction shows the formed nanoparticles are crystalline in nature and EDS confirms the formed nanoparticles are of gold. This shows P. juliflora seedling can synthesis different shapes of well dispersed nanoparticles.
Keywords: Gold; Nanoparticles; Prosopis juliflora; Shapes; synthesis; TEM